KUA's Communication Strategy in Revitalizing the Strengthening of the Marriage Record Program - Dina Puspita Sari; Elfi Yanti Ritonga (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
ABSTRACT The purpose of this study is to describe how the communication strategy applied in the Religious Office (KUA) in revitalizing the strengthening of the marriage record program in Percut Sei Tuan District, Deli Serdang Regency. This study uses a qualitative research method with a descriptive approach. The location of this research is the Office of Religious Affairs located on Jln. Besar Tembung No. 34, Percut Sei Tuan District, Deli Serdang Regency. The data used in this study is secondary data, in the form of policy archives and communication strategies in KUA, Percut Sei Tuan District, Deli Serdang Regency. Primary source, by conducting an in-depth interview with the head of KUA, Mr. Drs. Ahmad Sayuti Hasibuan, MA and Mrs. Nuriastusya'diah, SE. M. Si as the staff/general executor at KUA Percut Sei Tuan Deli Serdang Regency. Data collection techniques through observation, interviews, and documentation. The results of the study show that the strategy used by the religious office in Percut Sei Tuan District, Deli Serdang Regency, to revive and improve the marriage registration program. As everyone knows, socialization is the process by which norms, values, and behaviors are passed down from one generation to the next in a group or community. The KUA revitalization strategy is carried out to improve the strengthening of the program at KUA Percut Sei Tuan Deli Serdang Regency and the socialization of prospective brides. Keywords: Communication Strategy, KUA, Program Revitalization.